PENGARUH FAKTOR BAURAN PEMASARAN TERHADAP MINAT UNTUK MENJALANI OPERASI PADA PASIEN NYERI TULANG BELAKANG DI RS INDRAJANA PADA TAHUN 2023 - Dimas Rahman Setiawan; Yuli Prapanca; Nurminingsih (Transpublika Publisher, 2023)
The objective of this research is to determine the influence of marketing mix factors on the interest in undergoing surgery among patients with back pain at RS Indrajana in 2023. This research adopts a quantitative study with a cross-sectional design. The study was conducted at RS Indrajana in July 2023, and the research population consisted of 112 patients. The sampling technique used was purposive sampling. The research instrument employed a questionnaire with closed-ended questions and predefined response scales. Data analysis was carried out using univariate, bivariate, and multivariate methods. The research results indicate that there is a relationship between the marketing mix elements of product (p=0.036), price (p=0.000), promotion (p=0.005), people (p=0.000), and process (p=0.034) with the interest in undergoing surgery. The most dominant factors based on multivariate analysis are the marketing mix elements of people (p-value 0.043 < 0.05) and price (p-value 0.018 < 0.05). In conclusion, the marketing mix elements of product, price, promotion, people, and process have an influence on the interest of patients with back pain to undergo surgery at RS Indrajana in 2023. The marketing mix elements of people and price are the most dominant factors.